Incidence, risk factors and impact of seasonal influenza in pregnancy: A national cohort study. - Nicola Vousden; Kathryn Bunch; Marian Knight; UKOSS Influenza Co-Investigators Group (PLoS ONE)
Background Pregnant women are particularly vulnerable to severe infection from influenza resulting in poor neonatal outcomes. The majority of evidence relates to pandemic 2009 A/H1N1 influenza. The objective of this study was to describe the characteristics and outcomes of pregnant women hospitalised with seasonal influenza. Methods This national, prospective, observational cohort study used the UK Obstetric Surveillance System (UKOSS) to identify all pregnant women admitted to hospital between 01/11/2016 and 31/10/2018 with laboratory confirmed influenza at any gestation and up to two days after giving birth. These were compared to women admitted to give birth that did not have influenza. Baseline characteristics, immunization status, maternal and perinatal outcomes were compared. Results There were 405 women admitted to hospital with laboratory confirmed influenza in pregnancy: 2.7 per 10,000 maternities. Compared to 694 comparison women, women with influenza were less likely to be professionally employed (aOR 0.59, 95%CI 0.39-0.89) or immunised in the relevant season (aOR 0·59, 0·39-0·89) and more likely to have asthma (aOR 2.42, 1.30-4.49) or have had a previous pregnancy complication (aOR 2·47, 1·33-4·61). They were more likely to be admitted to intensive care (aOR 21.3, 2.78-163.1) and to have a cesarean birth (aOR 1·42, 1·02-1.98). Their babies were more likely to be admitted to neonatal intensive care (aOR 1.86, 1·01-3·42). Conclusions Immunization reduces the risk of hospitalisation with influenza in pregnancy which is associated with increased risk of morbidity for both the mother and baby. There is a continued need to increase awareness of safety and effectiveness of immunization in pregnancy and provision within antenatal care settings, especially for high-risk groups.